2005
DOI: 10.1117/12.592216
|View full text |Cite
|
Sign up to set email alerts
|

Viewing images on and off axis with CRT and LCD monitors: effects on observer and model performance

Abstract: CRT displays are generally used for softcopy display in the digital reading room, but LCDs are being used more frequently. LCDs have many useful properties, but can suffer from significant degradation when viewed off-axis. We compared observer performance and human visual system model performance for on and off-axis CRT and LCD viewing. 400 mammographic regions of interest with different lesion contrasts were shown on and off-axis to radiologists on a CRT and LCD. Receiver Operating Characteristic (ROC) techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…Additional information about the test conditions and observer performance results are provided elsewhere in this conference. 15 A signal template for the on-axis conditions was generated using the grayscale images after transforming them to luminance with the standard display function defined in DICOM Part 14 (which was also applied in the observer study). Another template for the off-axis conditions was created similarly after resampling the grayscale images horizontally by a factor of sin(45 deg) to simulate the off-axis appearance of those images.…”
Section: Methodsmentioning
confidence: 99%
“…Additional information about the test conditions and observer performance results are provided elsewhere in this conference. 15 A signal template for the on-axis conditions was generated using the grayscale images after transforming them to luminance with the standard display function defined in DICOM Part 14 (which was also applied in the observer study). Another template for the off-axis conditions was created similarly after resampling the grayscale images horizontally by a factor of sin(45 deg) to simulate the off-axis appearance of those images.…”
Section: Methodsmentioning
confidence: 99%
“…Recently we studied the effects on performance for viewing images on CRTs and LCDs on and off axis -since LCD displays have significant degradation in image quality as one views from any non-orthogonal position. 8 We found that the paired discrimination version of the model that we had used previously was able to predict correctly performance in the on-axis viewing condition but not in the off-axis condition. We therefore modified the model to a channelized version, taking more properties of the human visual system into account and found that we were able to predict successfully performance in both conditions.…”
Section: Introductionmentioning
confidence: 93%